Therapeutic Effect of Anti-Inflammatory Drugs and Vitamin C against Experimentally Induced Parkinson's Disease with Rotenone in Albino Mice - Ibrahim, Nagi Ali; Abdel-Salam, Omar Mohamed; Khadrawy, Yasser Ashry; Hashem, Amal Mohamed; Samir, Eman Mohamed (Medicine and Medical Research: New Perspectives Vol. 10, 2024)
Parkinson's disease is a brain disorder that causes unintended or uncontrollable movements, such as shaking, stiffness, and difficulty with balance and coordination. Symptoms usually begin gradually and worsen over time. As the disease progresses, people may have difficulty walking and talking. The nigrostriatal pathway is a dopaminergic pathway that connects the substantia nigra with the dorsal striatum. Loss of dopamine neurons in the substantia nigra is one of the main pathological features of Parkinson's disease, leading to a marked reduction in dopamine function in this pathway.